Estudo da cinética da hidrólise enzimática do óleo de soja: experimental e modelagem - Gurtat, Meline (2018)
The objective of this work was to evaluate the kinetic hydrolysis of soybean oil by action of the Lipozyme TL IM enzyme, especially the effect of the operational conditions such as water/oil molar ratio and temperature. In addition, to evaluate the capability of mathematical models to describe kinetic data including all compounds of the reaction (acylglycerols, glycerol, free fatty acids and water). Kinetic experiments, in batch reactor, were performed at different water/oil molar ratios (9:1, 20:1, 46:1 and 60:1) and temperatures (40, 52 and 64°C) under constant enzyme dosage (1% in relation to the oil mass) and stirring speed (250 rpm). The reaction yield was determined based on the free fatty acids concentration. Mathematical models based on the simplified Bi Bi Ping-Pong kinetic mechanism were used to describe kinetic data. The models were applied considering inhibition and non-inhibition by products of the reaction (without competitive inhibition; with inhibition by the free fatty acid; with inhibition by glycerol, with inhibition of both products). In the 46:1 and 60:1 water/oil molar ratios at temperatures of 52 and 64°C was achieved the higher reaction yield (77%). From the criterion of information Akaike and coefficient of determination values, it was verified that the mathematical model that consider non-inhibition by reaction products described better kinetic experimental data in all conditions. In addition, this model provided physically consistent results of the concentration profiles of the reaction compounds (triacylglycerols, diacylglycerols, monoacylglycerols, glycerol, free fatty acid and water).